Perfusion computed tomography in posterior circulation stroke: predictors and prognostic implications of focal hypoperfusion. (13th March 2018) - Pallesen, L.‐P.; Lambrou, D.; Eskandari, A.; Barlinn, J.; Barlinn, K.; Reichmann, H.; Dunet, V.; Maeder, P.; Puetz, V.; Michel, P.
Abstract : Background and purpose: The aim was to determine the predictors of focal hypoperfusion on computed tomography (CT) perfusion (CTP) in patients with acute posterior circulation stroke and its association with long‐term outcome. Methods: Patients with posterior circulation stroke were selected from the Acute Stroke Registry and Analysis of Lausanne (ASTRAL) who underwent CTP within 24 h of stroke onset as part of the stroke imaging protocol. Hypoperfusion was defined as an area of visually well demarcated mean transit time prolongation corresponding to an arterial territory on standard reconstruction CTP imaging maps. Areas of hypoperfusion were assessed with the posterior circulation Acute Stroke Prognosis Early CT Score. Clinical and imaging associations with focal hypoperfusion were identified using multiple imputation analyses, and the adjusted functional outcome measured by the modified Rankin Scale at 3 and 12 months was determined. Results: Of the 3595 consecutive patients from the ASTRAL registry between 2003 and 2014, 1070 (29.7%) had a posterior circulation stroke and 436 of these (40.7%) patients had a good quality baseline CTP. 23.1% had early ischaemic changes and 37.4% had focal hypoperfusion. In multiple imputation analysis, visual field deficits, reduced level of consciousness, cardiac and multiple stroke mechanisms, significant vessel pathology and ischaemic changes visible on plain CT were associated with focal hypoperfusion. Focal hypoperfusion was independently associated with outcome at 12 months (odds ratio 2.04, 95% confidence interval 1.22–3.42, P  < 0.01). Conclusions: In posterior circulation stroke patients undergoing acute CTP, multiple clinical, aetiological and radiological variables were associated with focal hypoperfusion. Patients with focal hypoperfusion had a worse 12‐month outcome.